DNA barcoding of mislabeled juvenile Tenualosa spp. as Gudusia chapra in the fish markets of Bangladesh (Bangladesh Journal of Scientific and Industrial Research, 2024)
Mislabeling of Juvenile hilsa, (Tenualosa spp.) or Jatka fish as Chapila (Gudusia chapra) is a recognized problem in Bangladesh resulting in fraudulence to consumers, illegal harvesting, and ultimately the degradation of hilsa fish production. We applied DNA barcoding using mitochondrial COX 1 gene together with morphometric analysis to resolve the mislabeling or misidentification of Clupeid fishes differentiating mainly hilsa fish from chapila fish. This study confirmed the identification of Jatka fish (Tenualosa sp.) that was mislabeled with chapila (Gudusia chapra). DNA barcoding identified the four species of clupeid fishes (Tenualosa ilisha, Gudusia chapra, Sardinella jussieu and Tenualosa toli) with phylogenetic placement. These cases may reflect a clear picture of admixture of locally sold mislabeled Jatka, which may warrant more comprehensive analyses. Mislabeling records of Juvenile hilsa established in the present study may also have implications for the harvesting, marketing and consumption the national fish of Bangladesh.Bangladesh J. Sci. Ind. Res. 59(2), 105-114, 2024